Zinc and cadmium complexes of a plant metallothionein under radical stress: desulfurisation reactions associated with the formation of trans-lipids in model membranes. - Torreggiani, Armida; Domenech, Jordi; Orihuela, Ruben; Ferreri, Carla; Atrian, Silvia; Capdevila, Merce; Chatgilialoglu, Chryssostomos (Chemistry (Weinheim an der Bergstrasse, Germany), 2009)
Metallothioneins (MTs) are sulfur-rich proteins capable of binding metal ions to give metal clusters. The metal-MT aggregates used in this work were Zn- and Cd-QsMT, where QsMT is an MT from the plant Quercus suber. Reactions of reductive reactive species (H(*) atoms and e(aq)(-)), produced by gamma irradiation of water, with Zn- and Cd-QsMT were carried out in both aqueous solutions and vesicle suspensions, and were characterized by different approaches. By using a biomimetic model based on unsaturated lipid vesicle suspensions, the occurrence of tandem protein/lipid damage was shown. The reactions of reductive reactive species with methionine residues and/or sulfur-containing ligands afford diffusible sulfur-centred radicals, which migrate from the aqueous phase to the lipid bilayer and transform the cis double bond of the oleate moiety into the trans isomer. Tailored experiments allowed the reaction mechanism to be elucidated in some detail. The formation of sulfur-centred radicals is accompanied by the modification of the metal-QsMT complexes, which were monitored by various spectroscopic and spectrometric techniques (Raman, CD, and ESI-MS). Attack of the H(*) atom and e(aq)(-) on the metal-QsMT aggregates can induce significant structural changes such as partial deconstruction and/or rearrangement of the metal clusters and breaking of the protein backbone. Substantial differences were observed in the behaviour of the Zn- and Cd-QsMT aggregates towards the reactive species, depending on the different folding of the polypeptide in these two cases.
Keywords: biomimetic chemistry; liposomes; metalloproteins; radical reactions; reaction mechanisms

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation